Hepcidin‐25/erythroferrone ratio predicts improvement of anaemia in haemodialysis patients treated with ferric citrate hydrate. Issue 8 (29th April 2019) - Hara, Masaki; Nakamura, Yuya; Suzuki, Hiroki; Asao, Rin; Nakamura, Masayuki; Nishida, Kazumasa; Kenmotsu, Sachiyo; Inagaki, Masahiro; Tsuji, Mayumi; Kiuchi, Yuji; Ohsawa, Isao; Goto, Yoshikazu; et al.
ABSTRACT: Background/Aims: Hepcidin‐25 (HEP‐25) and erythroferrone (ERFE) are key regulators of iron homeostasis. Correlations among serum ferritin, ERFE and HEP‐25 levels and improvements in anaemia have not been evaluated after administration of ferric citrate hydrate (FCH). Methods: This retrospective observational study investigated 24 patients on haemodialysis with both anaemia (haemoglobin (Hb) < 12 g/dL) and hyperphosphatemia (inorganic phosphorus ≥6 mg/dL). The patients who were administered FCH (1500 mg/day) for 12 consecutive weeks and 12 control patients who were administered a phosphate binder other than FCH were included. Correlations among Hb, HEP‐25 and ERFE levels were studied. We then stratified the FCH group into two subgroups using the median baseline values of ferritin, HEP‐25, ERFE and HEP‐25/ERFE ratio to predict whether these markers could serve as prognostic indicators in the treatment of anaemia. Results: In the FCH group, Hb, transferrin saturation, ferritin, HEP‐25 and ERFE levels were all significantly increased, while inorganic phosphorus levels, dosage of erythropoietin‐stimulating agent, and erythropoietin resistance index were all significantly decreased after drug administration. A significant inverse correlation was apparent between Hb and HEP‐25 levels, and a significant positive correlation was seen between Hb and ERFE levels. A significant inverse correlation was found between HEP‐25 and serum ERFE levels. Compared with the high HEP‐25/ERFE ratio group, only the low HEP‐25/ERFE ratio group exhibited significantly increased Hb levels at 12 weeks. Conclusion: HEP‐25/ERFE ratio could be a novel prognostic marker for increases in Hb levels following FCH administration. SUMMARY AT A GLANCE: Among patients on haemodialysis with both anaemia and hyperphosphatemia, hepcidin‐25/erythroferrone ratio could be a novel prognostic marker for increases in Hb levels following ferric citrate hydrate administration.